Direct cost analysis of renal replacement therapy in a Peruvian hospital - Arellan-Bravo, Luis (2024)
Introduction: Chronic kidney disease (CKD) is a public health problem in Peru. The Peruvian health system spends nearly 4% of its total budget just for paying only hemodialysis therapy. Objective: To determine a comparison of direct costs between kidney replacement therapy options. Materials and methods: This is a descriptive study for cost analysis. Costs for patients when using different modalities of kidney replacement therapy were assessed: renal transplant, hemodialysis, and peritoneal dialysis in Junin Health Network from Peruvian Social Security (EsSalud). Data from 213 patients was analyzed. Mean costs were calculated. Data was taken from the Acquisition and Cost Unit of the Junin Health Network in EsSalud from 2016 to 2021. Results: Renal transplant in the first year costs 70 680 PEN (US$ 18,123.07), and the cost is reduced as years go by. Afterwards, from the second year on the mean annual cost is US$ 6,000. Hemodialysis costs around 39,000 PEN per year (US$ 10,000), and peritoneal dialysis costs 49,680 PEN (US$ 12,738). At five years, peritoneal dialysis is more costly, followed by hemodialysis, and, finally, kidney transplant. Conclusions: Peritoneal dialysis is the most expensive therapy for CKD, followed by hemodialysis and renal transplant.